KEMAMPUAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMA NEGERI 8 PONTIANAK - Affrilia, Widhi; Syambasril, Syambasril; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research has purpose of this  study  was to determine and describe  the level of  writing ability in terms of structural aspects which include titlle, orientation, events, and re orientation. Linguistic aspects conjunction, reference word, adverb of time and verbs. This research uses descriptive method with quantitative research. The technic of the tests. Choosing sample is randomly The measurement of data collected is the ovestions of writing biographical text with the topic determined in advance. The research result of the ability of biographical text by students  class X SMA Negeri 8 in Pontianak that as follow: 1. The ability of writing the titlle of biographical text with percentage 96% are classifred good. 2. The ability in using orientation with percentage 100% are classified very good. 3. The ability in using events, with percentage 100%  are classified very good. 4. The ability in using re orientation with percentage 100%  are classified very good. 5. The ability in using conjunction with percentage 51% are classifred good. 6. The ability in using reference word  with percentage 13% are classifred good. 7. The ability in using adverb of time with percentage 5% are classifred good  8. The ability in using verbs with percentage 59% are classifred good. Based on the research has  done, specially ability in writing the content of biographical text with the percentage 67%, it is expceted that the teachers as educators can be more fokus to improving the ability of students to be able to give better performance.Keywords: Biographical Text, The Ability, Write,